Produção do ciclídeo neotropical Amatitlania sp. em sistema de recirculação: larvicultura e atividades alimentar e locomotora de animais em fase reprodutiva - Raphael Nogueira Bahiense (2021)
The convict cichlid (Amatitlania sp.) is considered an important species for the ornamental fish market. However, it is extremely territorial and little is known about its productive management in larviculture and its feeding and locomotion behavior. The objective of the study was to evaluate the production of young forms, as well as the feeding and locomotion behavior of Amatitlania sp. in a recirculating water system. Work was carried out to evaluate stocking density, feeding rate and feeding frequency in larviculture, and feeding behavior. For the evaluation of stocking density, 1500 post-larvae of Amatitlania sp. (2.22 ± 0.21 mg and 5.78 ± 0.27 mm, weight and total length, respectively), were kept in 24 tanks (3 L each), in a recirculation system, with a photoperiod of 12:12 h (light:dark), in an entirely randomized design, with six treatments (stocking densities: D1: 1 post-larvae L-1, D4: 4 post-larvae L-1, D8: 8 post-larvae L-1, D16: 16 post-larvae L-1, D32: 32 post-larvae L-1 and D64: 64 post-larvae L-1) and four repetitions (aquarium). This experiment lasted 28 days, with four weekly biometries. The test to evaluate feeding rate and feeding frequency was carried out with 768 post-larvae (2.01 ±0.19 mg and 5.69 ± 0.22 mm, weight and length, respectively), housed in 64 tanks (3 L each), in recirculation system, with photoperiod of 12: 12 h (light:dark), in an entirely randomized design, in a 4x4 factorial scheme, with four feeding rates (10, 30, 50 and 70% of the live weight of the animals per day) and four feeding frequencies (1, 2, 4 and 6 times per day), with four repetitions (aquariums). This stage lasted 35 days, with 5 weekly biometries. For both experiments, weight (FW), total (TL) and standard length (SL), animal height (H), specific growth rate (SGR), weight gain (WG), daily weight gain (DWG) and survival were evaluated. Animals at densities 1 and 4 post-larvae L-1 showed better results for survival, FW, WG and DWG. Animals fed 30, 50 and 70% of their live weight in feed showed the best results for TL and SL and best recovery after the air exposure test. Feeding frequencies of 2 and 4 times a day gave the best results for total and SL, FW, WG and DWG. The test to evaluate the feeding rate and locomotion was done in different social groups of Amatitlania sp., using 120 animals, distributed in four social groups, with six repetitions each, being: group 1 (1 male and 1 female per aquarium), group 2 (three males and three females); group 3 (six males per aquarium) and group 4 (six females per aquarium). Presence sensors were installed in the aquariums and connected to the feeders. The feeding (FA) and locomotor (LA) activities were evaluated using photoelectric sensors and automatic feeders. The growth of the animals was evaluated in all groups. After 30 days of the experiment the fish stabilized their demands, adjusting the consumption. Amatitlania sp. showed FA and LA predominantly diurnal, independent of the social group.